Energy Auditing For Lighting At The Building Faculty Of Science Universiti Teknologi Malaysia - Sharifah Fahsuhaizam Abd. Rahman, 1986-, author 536680; Universiti Teknologi Malaysia. Fakulti Sains 492720 (Johor Bahru, Johor : PENERBIT UTM PRESS, 2008)
Includes bibliographical references and index.